Benefits of adaptive reuse of old buildings - Mat Hasan, Hasni Suryani; Ab Wahab, Lilawati; Ismail, Dzulkarnaen; Abdul Rahim, Puteri Rohani Megat; Mat Hasan, Hasni Suhana (GADING Journal for the Social Sciences, 2023)
Much effort has been made to reduce, reuse, and recycle waste from almost everything to attain environmental sustainability. When buildings are abandoned and dilapidated, adaptive reuse can be a sustainable way to recycle and breathe new life into an old building. At the same time, appreciation and preservation of the architectural heritage’s significance can be sustained. An adaptively reused old building has been modified to manage the conversion of old services and technology to its new purpose or function as a result of development while preserving its original fabric and structure. The objective of this study is to identify the benefits of adaptive reuse. To achieve the objective, the data was obtained from previous literature, including journals and theses. It is believed that this study will assist organisations or individuals in achieving environmental sustainability through the adaptive reuse of old buildings. The study’s findings revealed that the adaptive reuse of old buildings benefits the environment and society. The outcome of this study is hoped to be a future reference for organisations or individuals interested in the adaptive reuse of old buildings.